INVESTIGATING THE EFFECT OF AUDITOR GENDER AND AUDITOR SIZE ON THE QUALITY OF AUDIT: AN APPLIED ANALYSIS OF BUSINESSES INDEXED ON IRAQ'S FINANCIAL REGULATOR - Ridha Mohammed Makttoof; Ali khudhatr Sameer; Murtadha Taha khudhair ALBadrani; Hussein Falah Hasan (Scholars Digest Publishing, 2025)
This work reveals the effect of both the auditor's gender and the auditor's size on the quality of the audit (auditor reputation and duration). To this end, 35 Iraqi local businesses were chosen from 2011 to 2021, the data of which were informed by the information published by corporations listed on Iraq's stock regulator (ISR). The results of the study found a statistical significance of both the size and the gender of the auditor on audit quality measured by the auditor's duration. Also, the study found a statistical significance of both size and the gender of the auditor on audit quality measured by the auditor's reputation.
Keywords: Auditor's biophysical characteristics, Auditor number, Audit features, Iraqi economy, Audit practices.